Ingesta de alimentos y su relación con factores socioeconómicos en un grupo de adultos mayores (2017)
ABSTRACT: To describe food intake and establish the correlation between some socioeconomic factors in a group of senior adults. Materials and Methods: Descriptive, cross-sectional study with 178 adults, ≥60 years old, who attended a dental consultation at Universidad de Antioquia between September 2014 and February 2015. Measurements for socio-demographic variables, frequency of food intake and food safety scale were obtained. The Chi-squared test was used to determine the association between food intake and socioeconomic variables. The categorical principal components analysis was used to determine feeding patterns. Results: About 50 % of the sample consumed dairy between one and three times a day, and meat, fruits and vegetables from one to two times. 74.7 % consumed cereals, bananas and tubers more than four times a day, which contrasts with dry grains and monounsaturated fat, whose frequency was less than once per day. Dairy and fruit intake had a significant association (p<0.05) with the following variables: economic income, stratum and food safety. Three dietary patterns known as "traditional varied diet", "unvaried" and "eating out of home" were identified, which explained the phenomenon in 12.8 %, 9.9 % and 8.4 %, respectively. Conclusion: The daily consumption of food groups in the elderly could be determined by the socioeconomic condition, being better in the medium stratum, who live in safe households and receive incomes. The pattern that explained the variability of consumption in greater proportion was the traditional varied diet.